A review of Echinacea - M Taghizadeh; S Jarvandi; N Yasa (Institue of Medicinal Plants, ACECR, 2002)
Echinacea is one of the most widely used medicinal herbs which is native to north America. The genus Echinacea consists of nine species, three of which E. angustifolia, E. pallida, and E. purpurea are used medicinally. Echinacea has been used for centuries, customarily as a treatment for the common cold, coughs, bronchitis, upper respiratory infections, and some inflammatory conditions. Although many of the active compounds of echinacea have been identified, the mechanism of action is not known. Studies show that the plant and its active component affect the phagocytic immune system, but not the specifically acquired immune system. Currently, Echinacea is being used to combat bacterial, viral, protozoan, and fungal infections, as an anti-inflammatory agent, and as an a possible chemopreventative agent.